Absolute palaeoreconstructions of continents based on palaeomagnetic poles and virtual geomagnetic poles? - Vizan, Haroldo (1997)
Transitional Jurassic and Early Cretaceous Virtual Geomagnetic Poles (VGPs) repositioned according to absolute palaeoreconstructions, define two paths similar to those for reversals ofthe last 12 Myr. These paths roughly coincide with the regions ofthe present core mantle boundary (CMB) that lie below regions ofthe lower-mantle with fast seismic wave velocities. A statistical test applied to the population of Jurassic-Early Cretaceous transitional VGPs identifies two antipodal bands (105/137° E-285/317’ E). Mantle convection and geoid models suggest that the present topographic temperature pattern over the CMB has persisted since the Late Paleozoic. Hotspot tracks are alternative tools to make absolute reconstructions, but they are not applicable to Late Paleozoic times due to lack ofhotspot framework for those times. Absolute reconstructions of South America for the Late Permian based on a mean palaeomagnetic pole and on the position of the bands defined by transitional and oblique VGPs are presented. These reconstructions are compared with an alternative obtained by a different method.